Egg quality determinants in cod (Gadus morhua L.): egg performance and lipids in eggs from farmed and wild broodstock - Salze, Guillaume; Tocher, Douglas R; Roy, William; Robertson, Derek (Aquaculture Research, 2005)
Lipids and essential fatty acids, particularly the highly unsaturated fatty acids, 20:5n-3 (eicosapentaenoic acid; EPA), 22:6n-3 (docosahexaenoic acid; DHA) and 20:4n-6 (arachidonic acid, AA) have been shown to be crucial determinants of marine fish reproduction directly affecting fecundity, egg quality, hatching success, larval malformation and pigmentation. In Atlantic cod (Gadus morhua L.) culture, eggs from farmed broodstock can have much lower fertilisation and hatching rates than eggs from wild broodstock. The present study aimed to test the hypothesis that potential quality and performance differences between eggs from different cod broodstock would be reflected in differences in lipid and fatty acid composition. Thus eggs were obtained from three broodstock, farmed, wild/fed and wild/unfed, and lipid content, lipid class composition, fatty acid composition and pigment content were determined and related to performance parameters including fertilisation rate, symmetry of cell division and survival to hatching. Eggs from farmed broodstock showed significantly lower fertilisation rates, cell symmetry and survival to hatching rates than eggs from wild broodstock. There were no differences in total lipid content or the proportions of the major lipid classes between eggs from the different broodstock. However, eggs from farmed broodstock were characterised by having significantly lower levels of some quantitatively minor phospholipid classes, particularly phosphatidylinositol. There were no differences between eggs from farmed and wild broodstock in the proportions of saturated, monounsaturated and total polyunsaturated fatty acids. The DHA content was also similar. However, eggs from farmed broodstock had significantly lower levels of AA, and consequently significantly higher EPA/AA ratios than eggs from wild broodstock. Total pigment and astaxanthin levels were significantly higher in eggs from wild broodstock. Therefore, the levels of AA and phosphatidylinositol, the predominant AA-containing lipid class, ...